(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Effective management strategies are essential for achieving success in any organization, whether in the corporate, non-profit, or public sector. The role of management extends beyond overseeing day-to-day operations; it involves strategic planning, leadership, and adapting to changing environments. This paper explores key management strategies that have proven successful across different industries, focusing on strategic planning, leadership, team development, innovation, and change management. The study identifies best practices and provides recommendations for managers to enhance organizational performance, maintain a competitive edge, and navigate challenges effectively.